Games Asyik Matematika: Pengabdian Kepada Masyarakat di SD Negeri Jatirangga 3 Bekasi - Dyah Anungrat Herzamzam; Evi Faujiah (Prima Abdika : Jurnal Pengabdian Masyarakat, 2021)
Based on the analysis of the situation that occurred, the lack of socialization related to the 2013 Curriculum made many elementary school teachers including SDN Jatirangga 3 Bekasi City do not understand. Teachers of SDN Jatirangga 3 in Bekasi City have not been able to apply the 2013 Curriculum in the learning process. Based on a request letter from SDN Jatirangga 3, the Chairperson of STKIP Kusuma Negara to send PGSD lecturers to provide training to teachers there regarding the 2017 Revised 2013 Curriculum in particular. So the PGSD Study Program, STKIP Kusuma Negara sent 4 lecturers to become resource persons for the training. This training was given the theme "Having Fun with the 2013 Curriculum". With the theme "Having Fun With Curriculum 2013", it is hoped that teachers will not make the specter of the 2013 Revised Curriculum 2017 as a frightening specter. Fun Indonesian Language Games will be the main material in community service activities this time. Service activities are carried out through several stages, the following are the steps that are carried out in service: 1) Planning, the following stages Observation and searching for data about the 2013 curriculum and various fun games-based learning methods, Collaboration with schools and teachers, PKM Game development Mathematics; 2) Implementation, implementation of the 2013 Curriculum Have Fun Training; 3) Application, Application of Curriculum 2013; 4) Evaluation and Assistance, Evaluation of the strengths and weaknesses of PKM. The evaluation uses an observation sheet at the time of implementing the 2013 curriculum in the classroom. The training activities which were carried out for 2 days ran smoothly even though there were obstacles and could be overcome immediately. The selection of speakers is adjusted to the field of expertise of each lecturer with an understanding of the 2013 Curriculum. The speakers' understanding of the 2013 Curriculum enables the training participants to understand the presentation of the speakers. It is marked by the enthusiasm of the training participants during the training activities. Math Fun Game in question is a method of learning mathematics in teams. Where the training participants were divided into 2 groups.